HUMANIZING OF ADMINISTRATIVE ACTIVITY - O. D. Garanina; A. A. Fedyashov (Научный вестник МГТУ ГА, 2016)
The article deals with determining the basic directions of humanizing the administrative activity in organization the content of which provides a constructive dialog in the «leader-subordinate» system based on taking into account of many-sided nature of a human being, social responsibility of management subject and object. Contradictions of this process conditioned estrangement of people in the vertical line of imperious relations, by displays of destructive qualities of human being are also described.